4 minutes rule in perimortem caeserean delivery: does it still relevant? Case series - Abdul Karim, Othman; Mohd Nazri, Ali; Wan Nasrudin, Wan Ismail (Global Journals, 2020)
To highlight the importance of immediate initiation of perimortem caesarean delivery in maternal with sudden cardiac arrest. Case report: We reported the outcomes of three cases of perimortem caesarean delivery secondary to maternal cardiac arrest. A 28-year-old G3P2 at 36 weeks of gestation who developed severe hypoxaemia secondary to acute pulmonary oedema which was arise from pre-eclampsia related hypertensive crisis.The second case was a 29-year-old G1P0 at 38 weeks of gestation who developed severe hypoxaemia secondary to spinal anaesthesia complication (total spinal)and the third case was a 44-yearold G5P4 at 39 weeks of gestation who developed severe hypoxaemia secondary to failed intubation and ventilation during induction of anaesthesia. Observing the outcomes of the three maternal after post perimortem caesarean delivery, we are strongly agreed that the time from maternal cardiac arrest to the initiation of resuscitative hysterotomy should be shifted from 4 minute to immediately. Conclusion: Preparations for perimortem caesarean delivery should be made simultaneously with the initiation of maternal resuscitative efforts.